A method for preparing high-performance nano-barium ferrite magnetic powder
By adding calcium oxide in the preparation process of barium ferrite magnetic powder and insulating coating of the modified water glass solution, the problems of poor chemical activity and uneven particle size of barium ferrite magnetic powder are solved, and high-performance and low-loss nanobarium ferrite magnetic powder are achieved.
Patent Information
- Application Number
- CN202411934636.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
The existing barium ferrite magnetic powder has poor chemical activity, large particle size and uneven particle size distribution. It is easy to appear gelatinous precipitation and particle agglomeration during the chemical co-precipitation process, resulting in unstable magnetic properties.
The grinding is carried out using calcium oxide to change the microstructure of barium ferrite, overcome its disadvantages of easy agglomeration, and insulating coating is carried out by modifying the hardness and adhesion of the water glass, and improving the surface structure of barium ferrite.
It improves the energy storage performance of barium ferrite, reduces losses, enhances its sum of magnetic properties, and significantly improves magnetic permeability and stability, reducing magnetic losses.
Smart Images

Figure BDA0005211200830000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials and relates to a method for preparing high-performance nano barium ferrite magnetic powder. Background Art
[0002] Barium ferrite, also known as barium ferrite magnetic powder, is a hard magnetic material with many unique magnetic properties. It can be used as permanent magnetic material, microwave absorption material, perpendicular magnetic recording material and magneto-optical recording material, etc. It has broad application prospects in the high-tech field. There are many methods to produce barium ferrite, such as ceramic process, glass crystallization process, hydrothermal synthesis process, chemical coprecipitation process, etc. The ceramic process is a common method for producing barium ferrite permanent magnetic materials. The process is mature, but the magnetic powder prepared by this method has poor chemical activity, large particle size, and different particle size distribution and appearance. The chemical coprecipitation method allows the materials to be mixed in an ionic state, the mixing is more uniform, and then the final product is obtained after precipitation, filtration and drying. The solid phase reaction can be fully completed at a lower calcination temperature. This method has the advantages of simple process, economy and easy industrialization. However, the disadvantage of this method is that colloidal precipitation often occurs during the precipitation process, which affects the subsequent filtration process. When the formula contains a small amount of doping elements, it is easy to cause agglomeration between particles, which makes it impossible to achieve uniform distribution and simultaneous precipitation of ions, which leads to uneven sintering particle size. Summary of the invention
[0003] The main purpose of the present invention is to provide a method for preparing high-performance nano-barium ferrite magnetic powder. The barium ferrite nano-magnetic powder obtained by the preparation method has the advantages of high performance and low loss.
[0004] The present invention adopts the following technical solutions to achieve the above purpose:
[0005] A method for preparing high-performance nano-barium ferrite magnetic powder mainly comprises the following steps:
[0006] Step A, after mixing iron oxide powder, zinc oxide powder, manganese oxide powder and calcium oxide powder, ball milling for 1.5-2h, heating to 500°C at a rate of 10°C / min and pre-sintering for 2h, cooling, adding barium carbonate powder, ball milling for a second time for 2.5-3h, heating to 500°C at a rate of 10°C / min and pre-sintering for 2h to obtain a primary product;
[0007] Step B, preparing a modified water glass solution: sodium tetraborate, sorbitol, toluenesulfonic acid, and water are mixed, sodium silicate is added, and the mixture is stirred for 1.5-2 hours, polyvinyl pyrrolidone is added, and after mixing, molten polyethylene glycol is added, mixed, and cooled to obtain a modified water glass solution;
[0008] Step C, insulation coating: mixing the initial product obtained in step A with the modified water glass solution obtained in step B, and mixing at 70-75° C. to obtain a coating;
[0009] Step D, mixing the coating obtained in step C with a release agent to form a ring-shaped blank with an outer diameter of 10-15 mm, an inner diameter of 5-8 mm, and a height of 4-6 mm, heating to 600°C at a rate of 10°C / min, keeping warm for 2 hours, cooling to room temperature, adding magnetic mesoporous silica nanoparticles after grinding, and mixing to obtain high-performance nano-barium ferrite magnetic powder.
[0010] Furthermore, in step A, the usage amount of each component is 30-50 parts by weight of iron oxide powder, 5-8 parts by weight of zinc oxide powder, 10-15 parts by weight of manganese oxide powder, 3-5 parts by weight of calcium oxide powder, and 10-15 parts by weight of barium carbonate powder.
[0011] Furthermore, in step A, the particle sizes of the components are 40-70 μm for iron oxide powder, 40-70 μm for zinc oxide powder, 40-70 μm for manganese oxide powder, 40-70 μm for calcium oxide powder, and 40-70 μm for barium carbonate powder.
[0012] Furthermore, in step B, the ingredients used are 0.1-0.15 parts by weight of sodium tetraborate, 0.05-0.1 parts by weight of sorbitol, 0.1-0.2 parts by weight of toluenesulfonic acid, 200-300 parts by weight of water, 10-15 parts by weight of sodium silicate, 1-1.5 parts by weight of polyvinyl pyrrolidone, and 3-5 parts by weight of polyethylene glycol.
[0013] Furthermore, in step C, the weight ratio of the initial product to the modified water glass solution is 1:(0.5-0.8).
[0014] Furthermore, in step D, the amount of the release agent added is 1%-2% of the weight of the coated material.
[0015] Furthermore, in step D, the release agent is barium stearate or silicone oil.
[0016] Furthermore, in step D, the amount of magnetic mesoporous silica nanoparticles added is 0.5%-0.8% of the mass of the coating material.
[0017] The present invention has the following beneficial effects:
[0018] In the preparation process of the barium ferrite of the present invention, calcium oxide is first added for grinding. The addition of calcium oxide can change the microstructure of the barium ferrite and overcome the disadvantage of easy agglomeration of the barium ferrite, thereby improving its energy storage performance, reducing losses, and improving the total magnetic properties of the barium ferrite. The modified water glass is used in the insulation coating to significantly improve the magnetic permeability of the barium ferrite and reduce magnetic losses. The addition of sodium tetraborate, sorbitol and other ingredients in the modification process of the water glass solution can adjust the hardness and adhesion of the water glass. When it is used for inorganic coating, it can also overcome the disadvantage of easy agglomeration of the barium ferrite, improve the surface structure of the barium ferrite, increase its formability during use, improve the stability of the secondary magnetic permeability, and reduce magnetic losses. DETAILED DESCRIPTION
[0019] The present invention is further explained below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent modifications to the present invention by those skilled in the art all fall within the scope of protection of the claims of this application.
[0020] Example 1
[0021] Step A, 30g of iron oxide powder (particle size 70μm), 8g of zinc oxide powder (particle size 70μm), 10g of manganese oxide powder (particle size 70μm), and 3g of calcium oxide powder (particle size 70μm) are mixed, ball-milled for 1.5h, placed in a resistance furnace and heated to 500°C at a rate of 10°C / min and pre-sintered for 2h, cooled, 15g of barium carbonate powder (particle size 70μm) is added, ball-milled for a second time for 2.5h, and placed in a resistance furnace again and heated to 500°C at a rate of 10°C / min and sintered for 2h to obtain a primary product;
[0022] Step B, preparing a modified water glass solution: 0.15 g of sodium tetraborate, 0.05 g of sorbitol, 0.2 g of toluenesulfonic acid, and 200 g of water are mixed, 10 g of sodium silicate is added, and the mixture is stirred for 2 h, 1 g of polyvinyl pyrrolidone is added, and after mixing, 5 g of molten polyethylene glycol is added, and the mixture is mixed and cooled to obtain a modified water glass solution;
[0023] Step C, insulation coating: 100 g of the initial product obtained in step A is mixed with 80 g of the modified water glass solution obtained in step B, mixed at 75° C., and dried to obtain a coating;
[0024] Step D, mix 100g of the coating obtained in step C with 2g of barium stearate to form a ring-shaped blank with an outer diameter of 15mm, an inner diameter of 8mm, and a height of 6mm, place the blank in a vacuum tube furnace, and heat it to 600℃ at a rate of 10℃ / min from room temperature (about 20℃), keep it warm for 2h, and then cool it to room temperature. After grinding, add 0.8g of magnetic mesoporous silica nanoparticles and mix well to obtain high-performance nano barium ferrite magnetic powder.
[0025] Example 2
[0026] Step A, 50g of iron oxide powder (particle size 40μm), 5g of zinc oxide powder (particle size 40μm), 15g of manganese oxide powder (particle size 40μm), and 5g of calcium oxide powder (particle size 40μm) are mixed, ball-milled for 2h, placed in a resistance furnace and heated to 500°C at a rate of 10°C / min and pre-sintered for 2h, cooled, 10g of barium carbonate powder (particle size 40μm) is added, ball-milled for a second time for 3h, and placed in a resistance furnace again and heated to 500°C at a rate of 10°C / min and sintered for 2h to obtain a primary product;
[0027] Step B, preparing a modified water glass solution: 0.1 g of sodium tetraborate, 0.1 g of sorbitol, 0.1 g of toluenesulfonic acid, and 300 g of water are mixed, 15 g of sodium silicate is added, and the mixture is stirred for 1.5 h, 1.5 g of polyvinyl pyrrolidone is added, and after mixing, 3 g of molten polyethylene glycol is added, and the mixture is mixed and cooled to obtain a modified water glass solution;
[0028] Step C, insulation coating: 100 g of the initial product obtained in step A is mixed with 50 g of the modified water glass solution obtained in step B, mixed at 70° C., and dried to obtain a coating;
[0029] Step D, mix 100g of the coating obtained in step C with 1g of silicone oil to form a ring-shaped blank with an outer diameter of 10mm, an inner diameter of 5mm, and a height of 4mm, place the blank in a vacuum tube furnace, and heat it to 600℃ at a rate of 10℃ / min from room temperature (about 20℃), keep it warm for 2h, and then cool it to room temperature. After grinding, add 0.5g of magnetic mesoporous silica nanoparticles and mix well to obtain high-performance nano barium ferrite magnetic powder.
[0030] Example 3
[0031] Step A, 40g of iron oxide powder (particle size 50μm), 6g of zinc oxide powder (particle size 50μm), 13g of manganese oxide powder (particle size 50μm), and 4g of calcium oxide powder (particle size 50μm) are mixed, ball-milled for 2h, placed in a resistance furnace and heated to 500°C at a rate of 10°C / min and pre-sintered for 2h, cooled, 13g of barium carbonate powder (particle size 50μm) is added, ball-milled for a second time for 2.5h, and placed in a resistance furnace again and heated to 500°C at a rate of 10°C / min and sintered for 2h to obtain a primary product;
[0032] Step B, preparing a modified water glass solution: 0.13 g of sodium tetraborate, 0.08 g of sorbitol, 0.15 g of toluenesulfonic acid, and 250 g of water are mixed, 13 g of sodium silicate is added, and the mixture is stirred for 2 h, 1.3 g of polyvinyl pyrrolidone is added, and after mixing, 4 g of molten polyethylene glycol is added, and the mixture is mixed and cooled to obtain a modified water glass solution;
[0033] Step C, insulation coating: 100 g of the initial product obtained in step A is mixed with 60 g of the modified water glass solution obtained in step B, mixed at 75° C., and dried to obtain a coating;
[0034] Step D, mix 100g of the coating obtained in step C with 1.5g of barium stearate to form a ring-shaped blank with an outer diameter of 13mm, an inner diameter of 7mm, and a height of 5mm, place the blank in a vacuum tube furnace, and heat it to 600℃ at a rate of 10℃ / min from room temperature (about 20℃), keep it warm for 2h, and then cool it to room temperature. After grinding, add 0.6g of magnetic mesoporous silica nanoparticles and mix well to obtain high-performance nano barium ferrite magnetic powder.
[0035] Comparative Example 1
[0036] 40g of iron oxide powder (particle size 50μm), 6g of zinc oxide powder (particle size 50μm), 13g of manganese oxide powder (particle size 50μm), and 13g of barium carbonate powder (particle size 50μm) are mixed evenly and ball-milled for 2h, placed in a resistance furnace and heated to 500℃ at a rate of 10℃ / min, and pre-sintered for 2h, cooled, 4g of calcium oxide powder (particle size 50μm) is added and mixed, ball-milled for 2h, ball-milled for a second time for 2.5h, and a 5% mass fraction of polyvinyl alcohol aqueous solution is added for granulation, and then a ring-shaped blank with an outer diameter of 13mm, an inner diameter of 7mm, and a height of 5mm is made. The blank is placed in a vacuum tube furnace, the starting temperature is room temperature (about 20℃), and the temperature is raised to 600℃ at a rate of 10℃ / min, kept warm for 2h, and then cooled to room temperature. After grinding, 0.6g of magnetic mesoporous silica nanoparticles are added and mixed to obtain high-performance nano-barium ferrite magnetic powder.
[0037] Comparative Example 2
[0038] Step A, 40g of iron oxide powder (particle size 50μm), 6g of zinc oxide powder (particle size 50μm), 13g of manganese oxide powder (particle size 50μm), and 13g of barium carbonate powder (particle size 50μm) are mixed, ball-milled for 2h, placed in a resistance furnace and heated to 500°C at a rate of 10°C / min, and pre-calcined for 2h, and cooled to obtain a primary product;
[0039] Step B, adding 4 g of sodium silicate to 60 g of water, and ultrasonically treating to obtain a sodium silicate aqueous solution; adding 100 g of the initial product obtained in step A, mixing at 75° C., and drying to obtain a coating;
[0040] Step C, mix 100g of the coating obtained in step B with 1.5g of barium stearate to form a ring-shaped blank with an outer diameter of 13mm, an inner diameter of 7mm, and a height of 5mm, place the blank in a vacuum tube furnace, and heat it to 600℃ at a rate of 10℃ / min from room temperature (about 20℃), keep it warm for 2h, and then cool it to room temperature. After grinding, add 0.6g of magnetic mesoporous silica nanoparticles and mix well to obtain high-performance nano barium ferrite magnetic powder.
[0041] Comparative Example 3
[0042] Step A, 40g of iron oxide powder (particle size 50μm), 6g of zinc oxide powder (particle size 50μm), 13g of manganese oxide powder (particle size 50μm), 4g of calcium oxide powder (particle size 50μm), and 13g of barium carbonate powder (particle size 50μm) were ball-milled for 2.5h, placed in a resistance furnace and heated to 500°C at a rate of 10°C / min and sintered for 2h to obtain a primary product;
[0043] Step B, preparing a modified water glass solution: 0.13 g of sodium tetraborate, 0.08 g of sorbitol, and 250 g of water were mixed, 13 g of sodium silicate was added, and the mixture was stirred for 2 h, 1.3 g of polyacrylamide was added, and after mixing, 4 g of sodium carboxymethyl cellulose was added, and the mixture was mixed and cooled to obtain a modified water glass solution;
[0044] Step C, insulation coating: 100 g of the initial product obtained in step A is mixed with 60 g of the modified water glass solution obtained in step B, and mixed at 75° C. to obtain a coating;
[0045] Step D, mix 100g of the coating obtained in step C with 1.5g of a release agent to form a ring-shaped blank with an outer diameter of 13mm, an inner diameter of 7mm, and a height of 5mm, place the blank in a vacuum tube furnace, and heat it to 600°C at a rate of 10°C / min from room temperature (about 20°C) for 2h, then cool it to room temperature and grind it to obtain high-performance nano-barium ferrite magnetic powder.
[0046] Performance Testing
[0047] The barium ferrite magnetic powders obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for properties such as magnetic permeability and magnetic loss.
[0048] The results are shown in Table 1 below.
[0049] From the results in Table 1, it can be seen that the barium ferrite obtained by the preparation method of the present invention has higher magnetic permeability and lower magnetic loss.
[0050] Table 1 Performance test results of different cobalt ferrites (100mT / 50kHz)
[0051]
Claims
1. A method for preparing high-performance nano-barium ferrite magnetic powder, characterized in that: The following steps are involved: Step A, after mixing iron oxide powder, zinc oxide powder, manganese oxide powder and calcium oxide powder, ball milling for 1.5-2h, heating to 500°C at a rate of 10°C / min and pre-sintering for 2h, cooling, adding barium carbonate powder, ball milling for a second time for 2.5-3h, heating to 500°C at a rate of 10°C / min and pre-sintering for 2h to obtain a primary product; Step B, preparing a modified water glass solution: sodium tetraborate, sorbitol, toluenesulfonic acid, and water are mixed, sodium silicate is added, and the mixture is stirred for 1.5-2 hours, polyvinyl pyrrolidone is added, and after mixing, molten polyethylene glycol is added, mixed, and cooled to obtain a modified water glass solution; Step C, insulation coating: mixing the initial product obtained in step A with the modified water glass solution obtained in step B, and mixing at 70-75° C. to obtain a coating; Step D, mixing the coating obtained in step C with a release agent to form a ring-shaped blank with an outer diameter of 10-15 mm, an inner diameter of 5-8 mm, and a height of 4-6 mm, heating to 600°C at a rate of 10°C / min, keeping warm for 2 hours, cooling to room temperature, adding magnetic mesoporous silica nanoparticles after grinding, and mixing to obtain high-performance nano-barium ferrite magnetic powder.
2. The preparation method according to claim 1, characterized in that: In step A, the usage amounts of the components are 30-50 parts by weight of iron oxide powder, 5-8 parts by weight of zinc oxide powder, 10-15 parts by weight of manganese oxide powder, 3-5 parts by weight of calcium oxide powder, and 10-15 parts by weight of barium carbonate powder.
3. The preparation method according to claim 2, characterized in that: In the step A, the particle sizes of the components are 40-70 μm for iron oxide powder, 40-70 μm for zinc oxide powder, 40-70 μm for manganese oxide powder, 40-70 μm for calcium oxide powder, and 40-70 μm for barium carbonate powder.
4. The preparation method according to claim 1, characterized in that: In step B, the ingredients used are 0.1-0.15 parts by weight of sodium tetraborate, 0.05-0.1 parts by weight of sorbitol, 0.1-0.2 parts by weight of toluenesulfonic acid, 200-300 parts by weight of water, 10-15 parts by weight of sodium silicate, 1-1.5 parts by weight of polyvinyl pyrrolidone, and 3-5 parts by weight of polyethylene glycol.
5. The preparation method according to claim 1, characterized in that: In the step C, the weight ratio of the initial product to the modified water glass solution is 1:(0.5-0.8).
6. The preparation method according to claim 1, characterized in that: In the step D, the amount of the release agent added is 1%-2% of the weight of the coated material.
7. The preparation method according to claim 6, characterized in that: In the step D, the release agent is barium stearate or silicone oil.
8. The preparation method according to claim 1, characterized in that: In the step D, the amount of magnetic mesoporous silica nanoparticles added is 0.5%-0.8% of the weight of the coating material.